Peran dan Tantangan Muslimat NU dalam Peningkatan Keagamaan Masyarakat di Sugihwaras Bojonegoro: The Role and Challenges of Muslimat NU in Enhancing Community Religious Life in Sugihwaras Bojonegoro - Izza Lailatul Maghfiroh; Wiwik Setiyani (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
Muslimat NU, as the largest women's organization in Nahdlatul Ulama, plays a central role in the religious development of the community. This study aims to analyze the roles, challenges, and strategies of Muslimat NU Sugihwaras in strengthening the religious life of the community. This study employs a descriptive qualitative approach, gathering data through in-depth interviews with Muslimat NU administrators and members. The analysis reveals the mechanisms through which the organization formulates and implements community religious programs. The findings indicate that Muslimat NU Sugihwaras performs three primary roles: (1) acting as an agent of religious education through routine study sessions and Majelis Taklim (religious study gatherings); (2) driving socio-religious activities through charitable initiatives and gatherings for women; and (3) safeguarding Ahlussunnah wal Jama’ah values ​​by promoting a moderate understanding of Islam within the community. However, the organization faces challenges, such as low participation among the younger generation and objections from some residents regarding the frequency of religious meetings. To address these issues, the organization employs strategies that include enhancing organizational understanding, innovating programs, and utilizing a persuasive approach toward the community. Through these strategies, Muslimat NU Sugihwaras maintains its relevance by adopting an adaptive, community-based approach. The organization's efforts to strengthen religious life are not limited to ritual dimensions alone but also encompass the social and economic aspects of the community.